An Attomolar-Level Optical Device for Monitoring Receptor–Analyte Interactions Without Functionalization Steps: A Case Study of Cytokine Detection - Nunzio Cennamo; Francesco Arcadio; Chiara Marzano; Rosalba Pitruzzella; Mimimorena Seggio; Maria Pesavento; Stefano Toldo; Antonio Abbate; Luigi Zeni (Sensors)
A plastic optical fiber (POF)-based device for biosensing strategies has been developed to monitor several protein–protein interactions at ultra-low concentrations without functionalization processes, exploiting plasmonic phenomena. In this work, novel tests were applied to different kinds of analyte–receptor interactions, such as interleukins, where the bioreceptor’s (protein antibody) molecular weight is roughly ten times that of the analyte (protein interleukin), while intracellular bioreceptors and small molecules at low molecular weight interactions have already been demonstrated via the same point-of-care test (POCT). The POCT was implemented by a white light source and a spectrometer connected via two POF-based chips connected in series: an innovative microcuvette chip and a D-shaped POF surface plasmon resonance (SPR) probe. In particular, the POF microcuvette chip was achieved by drilling three micro holes in the core of a modified POF. Instead of performing a functionalization step, the micro holes were filled with a specific receptor solution for the analyte (one microliter at the femtomolar level), which selectively captured the target (e.g., cytokine) when the samples were dropped over the filled micro holes (twenty microliters at the attomolar level). Three interleukins, IL-1β, IL-17A, and IL-18, were detected in the attomolar concentrations range by monitoring the resonance wavelength shift over time due to the cytokine/antibody (protein–protein) interaction. The POF-based device was proven to be effective for detecting several interleukins at the attomolar level in a few minutes and without functionalization processes.